Genomic loci associated with grain protein and mineral nutrients concentrations in Eragrostis tef under contrasting water regimes - Alemu, Muluken Demelie; Ben-Zeev, Shiran; Barak, Vered; Tutus, Yusuf; Cakmak, Ismail; Saranga, Yehoshua (Frontiers in Plant Science, 2024)
Climate change is becoming a global challenge, threating agriculture's capacity to meet the food and nutritional requirements of the growing population. Underutilized crops present an opportunity to address resilience to climate change and nutritional deficiencies. Tef is a stressresilient cereal crop, producing gluten-free grain of high nutritional quality. However, knowledge is lacking on tef's diversity of grain nutritional properties, their interaction with environmental conditions (e.g., water availability) and the underlying genomic loci. We assessed the effect of water availability on tef grain nutrient concentrations and identify the associated genomic loci. A collection of 223 tef genotypes, a subset of tef diversity panel 300 (TDP-300), were grown in the field under well-watered and water-limited conditions in 2021, and phenotyped for 11 traits including: grain protein and mineral concentrations and seed color.A genome-wide association study was conducted using 28,837 single-nucleotide polymorphisms (SNPs) and phenotypic data to identify marker-trait associations (MTAs). Tef grain nutrient concentrations exhibited wide genetic diversity with a significant influence of environment. Protein and most micronutrients were more concentrated under water-limited conditions, whereas most macronutrients were higher in the well-watered environment. A total of 59 SNPs were associated with one or more of the studied traits, resulting in 65 MTAs detected under both water treatments, and providing insights into the genetic basis of grain nutrients. Five SNPs reflected multiple associations, with four detecting the same trait under both treatments (multiple-environment effect), and one associated with both Zn and K (pleiotropic effect). In addition, two pairs of closely linked SNPs reflected multipleenvironment effects. While multiple-environment associations provide greater support for the integrity of these MTAs, the pleiotropic locus hints at a common mechanism controlling two mineral ions. The identified MTAs shed new light on the genomic architecture of tef's nutritional properties and provide the basis to enhance tef grain nutritional quality alongside drought resilience.